ALIH FUNGSI LAHAN PANGAN DI KABUPATEN PESAWARAN PROVINSI LAMPUNG - Widjaya, Sudarma (Universitas Sam Ratulangi, 2017)
AbstractLand conversion phenomenon is the greatest immediate threat to food security of the nation. Therefore, it necessary effort to prevent. The Regulation No. 41/2009 regarding a sustainable foodland protection aim to deal with the threat of foodland conversion. Those concerned about the current implementation of the policies relatively ineffective. This study aims to describes the spread of foodland, land conversion trend; to identify significant factor of foodland conversion and then formulate concept and strategy to deal with significant factors influencing foodland conversion in Pesawaran Regency, Lampung Province. This study was an exploratory and qualitative methods. Foodland are spread in all around Pesawaran Regency area. Due to the ownership of foodland by farmers are relatively small (0,50 hectares average). Foodland conversion had been for a long time, began with relatively low frequencies conveyance through a sale transaction. However, economic factors as driving forces of land conversion. In the strategy to deal with foodland conversion are strict enforcement The Regulation No.41/2009 through suitable policy began with establishing regional regulation of sustainable foodland protection and formulated several strategic plan with suitable budget policy. The implementation of regulation about foodland sale transaction system can be considered as a instrument to prevent land conversion with incentives for farmers through subsidy those increase land productivity and increasing community participation to defend sustainable foodland in order to gain sustainable prosperous living.Â Keywords: land conversion, sustainable foodland, foodland protectionÂ AbstrakFenomena alih fungsi lahan pangan sangat mengancam ketahanan dan kedaulatan pangan bangsa. Terbitnya Undang-Undang No. 41 Tahun 2009 Tentang Perlindungan Lahan Pertanian Berkelanjutan merupakan antisipasi dalam mengatasi alih fungsi lahan pertanian pangan. Masalah yang dihadapi adalah rendahnya efektifitas dalam implementasi kebijakan. Tujuan penelitian adalah untuk mendiskripsikan sebaran lahan pertanian pangan, kecenderungan alih fungsi lahan pangan; mengidentifikasi faktor penyebab dan merumuskan konsep serta strategi mengatasi alih fungsi lahan pangan di Kabupaten Pesawaran, Provinsi Lampung. Penelitian menggunakan metode ekploratif dan kualitatif. Lahan pertanian pangan tersebar di seluruh kecamatan Kabupaten Pesawaran. Pemilikan sawah kecil (rata-rata 0,50 ha). Alih fungsi lahan pangan sudah berlangsung cukup lama, diawali dengan pemindahan hak atas tanah melalui proses jual beli dengan frekuensi relatif rendah. Alih fungsi lahan pangan disebabkan oleh faktor ekonomi. Strategi untuk mengatasi alih fungsi lahan pangan adalah menindaklanjuti Undang-Undang No. 41/ Tahun 2009 melalui perumusan kebijakan yang tepat diawali dengan Penetapan Peraturan Daerah tentang perlindungan lahan pangan berkelanjutan dan penyusunan rencana strategis dalam implementasinya Pserta ditunjang kebijakan anggaran yang sesuai. Penerapan peraturan sistem jual beli lahan pangan dapat dipertimbangkan sebagai instrumen untuk pencegahan alih fungsi lahan pangan disertai pemberian insentif kepada petani berupa subsidi yang mampu meningkatkan kualitas lahan produktivitasnya, serta kebijakan pajak bagi petani yang mampu mempertahankan keberadaan lahan pangan berkelanjutan serta peningkatan partisipasi masyarakat mempertahankan lahan pangan secara berkelanjutan bagi keberlangsungan kehidupan yang sejahtera.Â Kata Kunci: alih fungsi lahan, lahan pangan berkelanjutan, perlindunga lahan pangan